KOMPETENSI MAKROSTRUKTUR MAHASISWA UNIDHA DILIHAT DARI FUNGSI HEMISFER KANAN - Handoko Handoko; Rahma Yanti Yanti; Rabbi Antaridha (Masyarakat Linguistik Indonesia Universitas Andalas, 2016)
Research on language competence of university students is critical since many people consider them have problem in well manner, especially in communication. Communication is not only passing information from speaker to hearer through language but also involve critical thinking and cognitive aspect of language. Macrostructure is competence which reflects speakers ability in using cognitive aspect to processing language. While microstructure is processed in left hemispher, macrostructure depends on process in right hemisphere. It is because macrostructure need holistic processing which connect partial informations and figure out the relation between the informations. Research toward students of Universitas Dharma Andalas shows that many students have problem in processing macrostructure aspect of language. About 81% participants have problem in summarizing, 75% participants have problem in memorizing adjective, 70% participants have problem in immidiate memory processing, 75% particiants have difficulty in figuring implicit relation, and 70% participants have difficult in using cohesion.